PERAN KEPALA SEKOLAH DALAM MEWUJUDKAN PROGRAM SEKOLAH ADIWIYATA - Fitria, Happy; Samsia, Samsia (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This research started from the condition in each school that lacks awareness of environmental preservation. Adiwiyata School aims to create a school community that cares and is cultured towards the environment. The only problem that remains is when students are asked about the Adiwiyata program there are still those who do not understand the program. This research uses descriptive qualitative research with data collection techniques in the form of observation, interviews and documentation. This research was conducted at SD Negeri 135 Palembang. The results showed that there are the programs a) Socialization of the implementation involved in the Adiwiyata program policies through meeting b) Make a green house or a nursery c) Making biopori infiltration holes d) There is a special room for processing waste with the 3R principle (Reuse, Reduce and Recycle) e) The existence of hydroponic plants, namely cultivation of plants using water f) Invate students to bring their own drinking bottles and eating places g) Competing in used materials h) Make Adiwiyata monument.